IMPLEMENTASI MOTODE RAPID APPLICATION DEVELOPMENT (RAD)PADA SISTEM INFORMASI PENGGAJIAN GURU HONOR - Titin Prihati; Syifah Fauziah (JUTIM (Jurnal Teknik Informatika Musirawas), 2020)
Payroll is one of the most important things where it is useful for information on the list and benefits received by employees whether in accordance with the duties, responsibilities and the level of effort that has been done for the job. The teacher is the main resource in the world of Education which is the main factor that successfully educates students at the school. So a faster, precise way to payroll teacher data is needed so a special program is needed to support the process. The RAD method is a model of the process of developing enhancements specifically for short work times. The existence of a payroll information system has been created, can provide fluency in the storage process and also input-data so that there is no difficulty in searching data, calculating and making reports.